Characterization of a de novo GABBR2 variant linked to autism spectrum disorder - Bielopolski, Noa; Stawarski, Michal; Roitman, Ilana; Fridman, Karen; Wald-Altman, Shane; Früh, Simon; Bettler, Bernhard; Nissenkorn, Andreea (Frontiers in Molecular Neuroscience, 2023)
GABAB receptors (GABABRs) are G protein-coupled receptors for γ-aminobutyric acid (GABA), the major inhibitory neurotransmitter in the central nervous system. Pathogenic variants in the GABBR1 and GABBR2 genes, which encode the GB1 and GB2 subunits of GABABRs, are implicated in several neurological and developmental disorders, including epilepsy and autism. Here we present a 7-year-old boy with Level 3 Autism Spectrum Disorder who carries a de novo heterozygous missense GABBR2 p.Arg212Gln variant. This variant was identified through whole exome sequencing and classified as variant of unknown significance (VUS). Treatment with the GABABR agonist baclofen showed no clinical improvement, raising the question whether this VUS is responsible for the patient’s phenotype. We conducted a study to investigate the impact of the GABBR2 p.Arg212Gln and the previously reported GABBR2 p.Arg212Trp variants on protein structure and receptor activity. This study utilized a combination of molecular dynamics (MD) simulations, and in vitro experiments. Our simulations demonstrate that both amino acid substitutions locally alter amino acid interactions in the extracellular domain of GB2. Most importantly, the substitutions influence the positioning of transmembrane helices, shifting the conformation towards an active state with GABBR2 p.Arg212Gln and an inactive state with GABBR2 p.Arg212Trp. Functional assays confirmed the MD predictions, as evidenced by increased constitutive activity and enhanced potency of GABA for GABBR2 p.Arg212Gln, and a decreased constitutive activity with a loss of GABA potency for GABBR2 p.Arg212Trp. Our findings demonstrate the utility of MD simulations in predicting the functional consequences of VUS. Clarifying the pathogenic mechanisms associated with gene variants will aid in the identification of personalized treatment approaches.